A Bibliometric Analysis of Halal Pharmaceuticals Consumer Behavior - Camelia Erliana Ru’yat (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The halal pharmaceutical industry is experiencing significant growth as consumer awareness and demand for Sharia-compliant products continue to rise. This study conducted a bibliometric analysis to examine research trends, influential authors, and key themes related to halal pharmaceutical consumer behavior. Using a dataset of 103 articles retrieved from Google Scholar, the study applied bibliometric methods, including performance analysis and science mapping, to identify research patterns. The findings revealed an increasing number of publications over the years, highlighting the growing academic interest in this field. Keyword co-occurrence analysis indicates that topics such as halal certification, consumer trust, and regulatory compliance are central themes in the literature, while emerging areas such as digital marketing and supply chain transparency present new research opportunities. The co-authorship analysis suggests that collaboration among researchers remains limited, indicating the need for greater interdisciplinary cooperation. Highly cited papers in this domain provide foundational insights but also reveal gaps in understanding the psychological and cultural factors influencing consumer behavior. This study contributes to the academic discourse on halal pharmaceuticals by mapping the current research landscape and offering recommendations for future studies.